The Impact of Government Health Expenditures on Economic Growth in Nigeria - Benjamin Olusola Abere (International Journal of Economics and Financial Management, 2026)
This study examined the impact of Government Health Expenditures and Economic Growth in Nigeria. The World Bank development indicators and the Central Bank of Nigeria (CBN) Statistical Bulletin provided the secondary data required for the analysis which used the ECM and Johansen Co- integration approach. The explanatory variables included the per capita real health care expenditure in the country, the percentage of the population aged 65 and over in the total population in the country and the share of public expenditure on health care in total health care expenditure in the country. The model of this study is built on Grossman’s Theory of Health Demand. The result of our findings reveals an inverse relationship between Gross Domestic Product and health care expenditure in country, in the long run while having a positive relationship in the short run. However, percentage of the population aged 65 and over in the total population in country and Gross Domestic Product both in the short and long run exhibit direct relationship. In addition, there is inverse relationship between the share of public expenditure on health care in total health care expenditure in country and Gross Domestic Product in the short run while having a positive relationship in the long run. The study therefore conclude that policies should be put in place by the government to partner with world health organization (WHO) in solving some fundamental health problems. Government should aim at reducing inequality by putting policies in place to bridge the gap between the rich and the poor, this would reduce monopoly power and bring about more equitable allocation of resources in the society which will lead to improvement in health outcomes hence a better quality of life.